Clinical and pathologic factors associated with subclinical spread of invasive melanoma - Shin, Thuzar M.; Shaikh, Waqas R.; Etzkorn, Jeremy R.; Sobanko, Joseph F.; Margolis, David J.; Gelfand, Joel M.; Chu, Emily Y.; Elenitsas, Rosalie; Miller, Christopher J. (Journal of the American Academy of Dermatology, 2017)
Indications to treat invasive melanoma with Mohs micrographic surgery (MMS) or analogous techniques with exhaustive microscopic margin assessment have not been defined. Identify clinical and histologic factors associated with subclinical spread of invasive melanoma. This retrospective, cross-sectional study evaluated 216 invasive melanomas treated with MMS and melanoma antigen recognized by T cells 1 immunostaining. Logistic regression models were used to correlate clinicopathologic risk factors with subclinical spread and construct a count prediction model. Risk factors associated with subclinical spread by multivariate analysis included tumor localization on the head and neck (OR 3.28, 95% confidence interval [CI] 1.16-9.32), history of previous treatment (OR 4.18, 95% CI 1.42-12.32), age ≥65 (OR 4.45, 95% CI 1.29-15.39), and ≥1 mitoses/mm2 (OR 2.63, 95% CI 1.01-6.83). Tumor thickness and histologic subtype were not associated with subclinical spread. The probability of subclinical spread increased per number of risk factors, ranging from 9.22% (95% CI 2.57%-15.86%) with 1 factor to 80.32% (95% CI 68.13%-92.51%) with 5 factors. This study was conducted at a single academic institution with a small study population using a retrospective study design that was subject to potential referral bias. Clinical and histologic factors identify invasive melanomas that are at increased risk for subclinical spread and might benefit from MMS or analogous techniques prior to reconstruction.